Surgical technique for knee osteoarthritis induction in New Zealand white rabbits - Abu Hassan, Salmah Anim; Zulkifly, Ahmad Hafiz; Abd. Rahim, Nour El Huda; Mohamad Amri, Nur Fathonah; Hassan, Habibah; Mohd Jan, Nurul Hafiza; Ibrahim, Mohd Zulfadzli; Mohd Zohari, Sarah Haryati; Zainal Abdullah, Muhamad Ezham; Che Seman, Che Zarida; Abdul Hamid, Zahana; Abdul Jalil, Rosnani (2023)
INTRODUCTION: Osteoarthritis (OA) is a degenerative joint disease that affects both humans and animals. It is characterized by the progressive deterioration of the cartilage an underlying bone. Surgical techniques are often used in animal models of OA to study the disease progression. MATERIALS & METHODS: Thirty-three New Zealand White rabbits (NZWR) weighing about 2.5 kg to 3.5 kg were chosen. Both foreleg knee joints were destabilized by anterior cruciate ligament transection (ACLT). Subsequently, medial and lateral partial meniscectomy and scraping both cartilage of tibial condyles was done. RESULTS: Osteoarthritis induction was successfully created in all 33 rabbits, evidenced by radiograph as early as 3 weeks. Radiographic images at 6 and 12 weeks showed consistent progression to moderate and severe osteoarthritis. Post surgical survival rate was 100%. DISCUSSIONS: NZWR are widely used in knee osteoarthritis studies because OA development in this species closely mimics the disease pathophysiology in humans. The combination of ACLT with partial meniscectomy ensures the formation of post traumatic osteoarthritis model by causing joint destabilization and inflammatory damage. As opposed to humans, rabbits have higher loading pressure in the lateral compartment of the knee joint. To imitate human knee OA which commonly involves the medial joint compartment, partial meniscectomy of the medial meniscus is important. Furthermore, as rabbit articular cartilage is known to be capable for regeneration, partial transection of both parts meniscus guarantees the formation of OA in the animal model. CONCLUSION: The surgical induction of knee osteoarthritis via ACLT combined with medial and lateral partial meniscectomy is a successful technique with a consistent result.